2018
DOI: 10.1108/josm-04-2018-0113
|View full text |Cite
|
Sign up to set email alerts
|

Customer experience challenges: bringing together digital, physical and social realms

Abstract: Purpose-The purpose of this paper is to explore innovations in customer experience at the intersection of the digital, physical and social realms. It explicitly considers experiences involving new technology-enabled services, such as digital twins and automated social presence (i.e. virtual assistants and service robots). Design/methodology/approach-Future customer experiences are conceptualized within a three-dimensional spacelow to high digital density, low to high physical complexity and low to high social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
407
1
30

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 586 publications
(446 citation statements)
references
References 117 publications
8
407
1
30
Order By: Relevance
“…2,3 However, in the context of developing countries, such as Jordon, such studies have remained few and far between. 4,5 Unlike European countries, Jordanian businesses are not required to seek permission from customers before carrying out a mobile marketing campaign. However, it was observed that the gaining of customer permission, and the positive marketing of Jordon's Zain Telecomin, delivered optimistic responses from 1.9 million subscribers.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 However, in the context of developing countries, such as Jordon, such studies have remained few and far between. 4,5 Unlike European countries, Jordanian businesses are not required to seek permission from customers before carrying out a mobile marketing campaign. However, it was observed that the gaining of customer permission, and the positive marketing of Jordon's Zain Telecomin, delivered optimistic responses from 1.9 million subscribers.…”
Section: Introductionmentioning
confidence: 99%
“…Digitalization plays an important role on creating good words of mouth. Digital customer experience has significant effect on customer satisfaction (Joshi, 2018) by providing better customer value (Bolton et al, 2018;Klaus, 2014). It provides better experience for customers through digitalization (Betzing et al, 2018) which influence on brand image, significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Dacko (2017) then identifies increased value from retail settings when the shopping experience is enriched by the mobile augmented reality shopping apps. The phenomenon of bringing digital, physical and social realms together was also examined by Bolton et al (2018) and they state that experience can be improved this way, but that companies will face difficult trade-offs between the efficiency and effectiveness of digital technologies if they would focus on value proposition during interactions with customers. Wang et al (2018) discovered that higher customer experience levels (time between purchase and online review and intensity of usage) are associated with a decrease in customer satisfaction and that both price and popularity have important effects on the relationship between customer experience and satisfaction, because, for example, quality and price are highly correlated.…”
Section: Results and Discussion Primary Research Findingsmentioning
confidence: 99%